SIFAT FISIK TANAH PADA BERBAGAI JARAK DARI SALURAN APLIKASI LIMBAH CAIR PABRIK KELAPA SAWIT - Friska Anggreani Silalahi; Nelvia Nelvia (DINAMIKA PERTANIAN, 2017)
This research aimed to study the effect of the application of waste of palm oil factory liquid on the soil physical characteristic of palm oil plantations. The application of waste of palm oil factory liquid done on a tract the application of which is called by the land application (LA) and LA have been made over 8 years. The research conducted inland of palm oil plantation Batubara Regency, North Sumatra Province from August to November 2015. The method used in this research was survey method. Determination of the sampling and research location was done deliberately by the purpose of the research (purposive sampling). Soil samples for analysis of soil physical characteristic were taken from distance 1, 2, 3, 4, and 5 meters from canal application of palm oil factory liquid waste or land application (LA) with 0-10 cm, 10-20 cm and 20-30 cm depth each other taken from 5 points, included two on the right and left upper of LA and two on the right and left downstream of LA, and without LA used as a control. The results showed that the application of waste of palm oil factory liquid to decreases bulk density and increase the total pore space, water content, permeability and C-organic of soil of oil palm plantations compared to control at a distance 1 meter from LA and decreased with the farther the distance LA (5 m) and deeper (0-30cm), but will not affect particles density.